Optimal Management of Riata Leads with No Known Electrical Abnormalities or Externalization: A Decision Analysis. (28th November 2014) - POKORNEY, SEAN D.; ZHOU, KE; MATCHAR, DAVID B.; LOVE, SEAN; ZEITLER, EMILY P.; LEWIS, ROBERT; PICCINI, JONATHAN P.
Riata Decision Analysis Introduction Riata and Riata ST implantable cardioverter‐defibrillator (ICD) leads (St. Jude Medical, Sylmar, CA, USA) can develop conductor cable externalization and/or electrical failure. Optimal management of these leads remains unknown. Methods and Results A Markov model compared 4 lead management strategies: (1) routine device interrogation for electrical failure, (2) systematic yearly fluoroscopic screening and routine device interrogation, (3) implantation of new ICD lead with capping of the in situ lead, and (4) implantation of new ICD lead with extraction of the in situ lead. The base case was a 64‐year‐old primary prevention ICD patient. Modeling demonstrated average life expectancies as follows: capping with new lead implanted at 134.5 months, extraction with new lead implanted at 134.0 months, fluoroscopy with routine interrogation at 133.9 months, and routine interrogation at 133.5 months. One‐way sensitivity analyses identified capping as the preferred strategy with only one parameter having a threshold value: when risk of nonarrhythmic death associated with lead abandonment is greater than 0.05% per year, lead extraction is preferred over capping. A second‐order Monte Carlo simulation (n = 10, 000), as a probabilistic sensitivity analysis, found that lead revision was favored with 100% certainty (extraction 76% and capping 24%). Conclusions Overall there were minimal differences in survival with monitoring versus active lead management approaches. There is no evidence to support fluoroscopic screening for externalization of Riata or Riata ST leads.